Comparative Profiling of Metastatic 4T1- vs. Non-metastatic Py230-Based Mammary Tumors in an Intraductal Model for Triple-Negative Breast Cancer - Steenbrugge, Jonas; Vander Elst, Niels; Demeyere, Kristel; De Wever, Olivier; Sanders, Niek N.; Van Den Broeck, Wim; Dirix, Luc; Van Laere, Steven; Meyer, Evelyne (Frontiers in Immunology, 2019)
The transition of ductal carcinoma in situ (DCIS) to invasive carcinoma (IC) in breast cancer can be faithfully reproduced by the intraductal mouse model. Envisaging to use this model for therapeutic testing, we aimed to in-depth characterize the tumor immunity associated with the differential progression of two types of intraductal tumors. More specifically, we focused on triple-negative breast cancer (TNBC) and intraductally inoculated luciferase-expressing metastatic 4T1 and locally invasive Py230 cells in lactating mammary glands of syngeneic BALB/c and C57BL/6 female mice, respectively. Although the aggressive 4T1 cells rapidly formed solid tumors, Py230 tumors eventually grew to a similar size through enhanced proliferation. Yet, ductal tumor cell breakthrough and metastasis occurred earlier in the 4T1- compared to the Py230-based intraductal model and was associated with high expression of matrix metalloproteinase (MMP)-9, vascular endothelial growth factor (VEGF), chitinase 3-like 1 (CHI3L1) and lipocalin 2 (LCN2) as well as an increased influx of immune cells (mainly macrophages, neutrophils and T-cells). Moreover, activated cytotoxic T-cells, B-cells and programmed death-1 (PD-1)-positive cells were more prominent in the 4T1-based intraductal model in line with enhanced pro-inflammatory cytokine and gene expression profiles. Py230-based tumors showed a more immunosuppressed anti-inflammatory profile with a high amount of regulatory T-cells, which may account for the decreased T-cell activation but increased proliferation compared to the 4T1-based tumors. Taken together, our results highlight the differential immunological aspects of aggressive metastatic and non-aggressive intraductal progression of 4T1- versus Py230-based tumors, providing a base for future studies to explore therapy using these intraductal TNBC models.